Tengkawang cultivation model in community forest using agroforestry systems in West Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2017)
Winarni B, Lahjie AM, Simarangkir B.D.A.S, Yusuf S, Ruslim Y.2017. Tengkawang cultivation model in community forest using agroforestry systems in West Kalimantan, Indonesia. Biodiversitas 18: 765-772. Tengkawang is the flora mascot of West Kalimantan and has long been supporting the life of people around the forest. Its fruit can be processed into fat which traded as ‘green butter', ‘borneo tallow', or ‘tengkawang oil', which used as cocoa butter substitutes and the material for manufacturing lipstick, candle and drugs. Its wood was used as raw material for sawmill and plywood industries. Today, tengkawang tree existence is endangered and has been replaced with rubber plantations. The purposes of this research were to: (i) analyze the maximum growth increment of tengkawang; (ii) analyze the maximum production of tengkawang fruits and latex; (iii) analyze the financial feasibility of tengkawang cultivation and tengkawang combined with rubber; and (iv)formulate tengkawang cultivation model. The research used a descriptive method in survey form and interview technique by using questionnaire. The research result showed that the maximum growth increment of tengkawang which cultivated in monoculture (model 1) and tengkawang combined with rubber (model 2) were achieved at the age of 40 years. The maximum production of tengkawang fruit in model 1 and model 2 were achieved at the age of 64 years, while the maximum production of latex (model 2) was achieved at the age of 17 years. The cultivation of tengkawang by model 1 produced IRR of 12.3% and model 2 produced IRR of 12.9%. Financially, both cultivation models of tengkawang were feasible to be cultivated. Financially, tengkawang cultivation by using rubber in an agroforestry system was more profitable than tengkawang cultivation in monoculture.
Keywords: Financial analysis; increment; production analysis; tengkawang